Income inequality in the post-2000 era: Development, globalization, and the state. (May 2020) - Clark, Rob
During the late 20th century, income inequality rose in most countries around the world, and by a substantial amount in some cases. By contrast, income disparities have stabilized during the post-2000 era, and have even begun to decline in a small majority of states. What accounts for this recent change? Unfortunately, existing work is not well-positioned to address this question. Researchers commonly restrict their attention to affluent nations or use empirical models that have not kept pace with either the changing landscape or the availability of newer measures, all of which suggests a path forward in this area of research. This article focuses on the post-2000 era, drawing from a large global sample (1284 observations across 129 states), while utilizing novel measures that better reflect the contemporary period. The study reports results from Prais–Winsten regression with panel-corrected standard errors and two-way fixed effects. The models show that income inequality is shaped by the major employment sectors (agriculture, industry, and services), the relative supply of unskilled/skilled labor (as indicated by population growth and tertiary school enrollment, respectively), globalization (international trade and migration), state characteristics (the size of government and regulation of labor), gender dynamics (female participation in paid work and government), and the unemployment rate. In sum, the results reveal a set of equalizing and disequalizing factors that shape each country's income distribution.